Kedudukan Asas Konsensualisme dalam Transaksi Terapeutik antara Dokter dengan Pasien - Efendi, Nuril Hikam (Universitas Jember, 2023)
Doctors have the main task of maintaining and caring for patients who are experiencing a decline in health. The private relationship between a doctor and a patient is known as a therapeutic transaction, which can be understood as a relationship established because it is based on the trust that exists between the doctor and the patient regarding medical actions or treatment measures. Medical action or treatment for a patient must be preceded by approval. Consent is the implementation of the patient's will to get treatment. However, with the consent of the will, it cannot be interpreted as meaning that an agreement is automatically established between the doctor and the patient. Doctors and patients who have a relationship within the scope of medical action must be analyzed and studied systematically, so that from this description the researcher focuses on the formation of therapeutic transactions based on the principle of consensualism in the doctor-patient relationship. The purpose of this study is to determine the concept of engagement and the position of consensualism in therapeutic transactions. The research method used in this study is normative juridical research, which is based on a review of literature and regulations or public policies that are appropriate to the problems studied. The results of the study show that the principle of consensualism has a fundamental position and must exist in every act of treatment by doctors on patients.Keywords: Therapeutic, Consent, Medical Personnel, Patients.